Enhancing resilience: implementing resilience building policies against major industrial accidents. (1st January 2013) - Labaka, Leire; Hernantes, Josune; Laugé, Ana; Sarriegi, Jose María
The proper functioning of critical infrastructures (CIs) is vital for society's welfare. A disruption in one of them may lead to a crisis that affects not only the CI where the triggering event occurs but also the whole society. Therefore, it is fundamental to increase the whole system's resilience level. This paper defines resilience as the capacity of a system to prevent a crisis occurrence, to reduce the consequences from failure, and to recover rapidly and efficiently. Although there is much information about the definition of resilience, literature still lacks to provide a detailed holistic prescription about what activities should be carried out to improve the resilience level of the CIs and the society as a whole. This paper defines twelve policies that help to enhance the resilience level of all the stakeholders involved in crisis management, using information gathered from experts and examining several case studies.